2012
DOI: 10.1007/s10461-011-0097-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Late Presentation for HIV Diagnosis: A Literature Review and Suggested Way Forward

Abstract: Early commencement of antiretroviral treatment can be beneficial and economical in the long run. Despite global advances in access to care, a significant proportion of adults presenting at HIV/AIDS care facilities present with advanced HIV disease. Understanding factors associated with late presentation for HIV/AIDS services is critical to the development of effective programs and treatment strategies. Literature on factors associated with late presentation for an HIV diagnosis is reviewed. Highlighted is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
76
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 140 publications
6
76
1
5
Order By: Relevance
“…On the other hand, although PITC services were considered acceptable by patients, male respondents expressed fear and stress involved with HIV testing, in particular when the testing is not planned or anticipated. Several studies on counseling and testing have observed similar findings of stressful experiences accompanying HIV-testing (Osterman et al, 2011;Mukolo et al, 2013;Musheke et al, 2013;UNAIDS, 2012UNAIDS, ,2013.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…On the other hand, although PITC services were considered acceptable by patients, male respondents expressed fear and stress involved with HIV testing, in particular when the testing is not planned or anticipated. Several studies on counseling and testing have observed similar findings of stressful experiences accompanying HIV-testing (Osterman et al, 2011;Mukolo et al, 2013;Musheke et al, 2013;UNAIDS, 2012UNAIDS, ,2013.…”
Section: Discussionmentioning
confidence: 71%
“…Opportunity for earlier detection, early initiation of treatment and care and risk reduction strategies provided by PITC services were perceived highly by most respondents. The benefits of VCT services have been documented elsewhere by Anderson et al (2008), Shorter et al (2009), Mukolo et al (2013) and Musheke et al (2013. They have also been observed as entry points into couple counseling and increased HIV sero-status disclosure among couples (Becker et al, 2010;Kelley et al, 2011;Njau et al, 2012). This observation therefore calls for health care providers to maintain high level of confidentiality and patient care and explore the opportunity for couple counseling and promote disclosure among couples.…”
Section: Discussionmentioning
confidence: 92%
“…The profile of people who did not know their HIV status before diagnosis were patients younger than 25 years or those older than 44 years and who had heterosexual sex (7,8) . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Numerous studies developed in Spain have shown a high frequency of sexual risk behaviors among young heterosexuals and homosexuals (9)(10)(11)(12)(13)(14)(15), but few studies have examined the frequency of HIV antibody testing and determinants of delayed diagnosis (16). According to the Survey on Health and Sexual Habits conducted by the National Statistics Institute, only 10.4 % of the population in Spain has been tested voluntarily to find out their HIV status (17).…”
mentioning
confidence: 99%
“…Considering the contributions of social-cognitive models, multiple variables influence preventive behavior and it is necessary to explore them to understand the HIV antibody testing behavior (16). Thus, the Health Belief Model indicates the influence of perceived susceptibility to illness, perceived severity of the disease and the benefits and barriers involved in carrying out preventive behavior (25).…”
mentioning
confidence: 99%
“…9 Timely screening (and treatment) is important, as older people are more likely to experience late-stage clinical diagnosis. [10][11][12] Delayed diagnosis may increase the likelihood of forward transmission, as well as the severity of symptoms and treatment difficulties. Asymptomatic screening of all older people, however, would not be appropriate given the relatively low prevalence of STIs.…”
Section: Introductionmentioning
confidence: 99%